2000
DOI: 10.1063/1.874154
|View full text |Cite
|
Sign up to set email alerts
|

Laser induced electron acceleration in the presence of static electric and magnetic fields in a plasma

Abstract: Results of a fully relativistic three-dimensional (3-D) single particle code, supported by a theoretical model, on direct laser acceleration of electrons in radial electric and azimuthal magnetic static fields are presented. The ponderomotive force and the longitudinal components of the laser field are taken into account in the code. The electron motion in the static fields is similar to the motion in a magnetic wiggler. At resonance, when the bounce frequency of the wiggling motion is within a few percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 25 publications
7
62
0
Order By: Relevance
“…Furthermore, it is found that most of the electron energy gain is due to the transverse laser electric field with the laser magnetic field converting the transverse momentum into longitudinal one. 37,38 More recently, a similar analysis has been performed for the experiment described in Ref. 19, which in contrast to our results indicates that most of the fast electrons are produced via longitudinal acceleration due to the plasma wakefield.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Furthermore, it is found that most of the electron energy gain is due to the transverse laser electric field with the laser magnetic field converting the transverse momentum into longitudinal one. 37,38 More recently, a similar analysis has been performed for the experiment described in Ref. 19, which in contrast to our results indicates that most of the fast electrons are produced via longitudinal acceleration due to the plasma wakefield.…”
Section: Discussionsupporting
confidence: 69%
“…19 might not have been enough time for the channel to fully develop and establish the quasi-static fields necessary for the DLA mechanism to become effective. 37,38 In recent years positrons have played an important role in applications in diverse fields of physics, e.g., surface physics, 52 positronium spectroscopy 53 and electron-positron plasmas. 54 Although for most of these applications conventional radioactive sources like 22 Na or 58 Co are currently used, the distinct possibility exists to replace them with laser driven positron sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At highly relativistic a 0 , the spectra become more Maxwellian, with a steadily increasing effective temperature T ef f for increasing a 0 . The thermalization could be due to phase rotation of electrons once they became dephased in a plasma wave, but is also a consequence of direct laser acceleration (DLA) mechanisms [7,12]. The variation of maximum electron energy and temperature T ef f with increasing a 0 though is strongly indicative of the presence of DLA.…”
Section: Pacs Numbers: Valid Pacs Appear Herementioning
confidence: 99%
“…We then verified that the SW alone is not able to accelerate electrons to energies as high as z = 200: indeed, when only keeping the SW electric field, we obtained electron energies no larger than z = 50, consistently with the trapped electron dynamics discussed above. We also considered the standard betatron acceleration [10,15]. This mechanism corresponds to retaining only the laser fields and the transverse charge separation field E CS in the equations of motion.…”
mentioning
confidence: 99%